PENDEKATAN STUDI ISLAM DALAM PERSPEKTIF MULTIKULTURAL - Syamsul Anwar; Kambali (CV. Adiba Aisha Amira, 2025)
Approach to Islamic Studies from a Multicultural Perspective. The Islamic study approach based on the view of multiculturalism is a paradigm in which Islam is part of the study of a pluralistic society which prioritizes tolerance and mutual respect for the differences that exist in society with different concepts of understanding Islam at the technical and practical levels in each region. The approach to Islamic studies in the theological aspect based on a multicultural view is an approach that prioritizes the washatiyah side, which implements the concept of mutual respect for diversity by finding a middle way based on peace, benefit and balance in life with fellow Muslims who are different in terms of religious ritual practices. The Islamic study approach to aspects of philosophy based on a multicultural view is an approach in which Islam does not separate aspects of philosophy that developed previously, where in terms of practicing Islamic beliefs it has a combination of philosophy between culture and Islam and has different varieties. So Islam must actually be able to combine different philosophical concepts for the good of society. The Islamic study approach to historical aspects based on a multicultural view emphasizes the historical acculturation aspect. Where in Islam it does not abandon existing past history, but instead history is the most important part of Islam and the development of Islam is due to its long history which is the motivation to survive until now. Likewise, when Islam applies to societies that have different histories, Islam connects their history as part of developing and advancing in civilization. The approach to Islamic studies in the sociological aspect is based on the multicultural view that Islam always respects differences in culture, race and ethnicity. Tolerance for differences is very high, so it is easily accepted in society, because the principle on which it is built is rahmatan lil alamin